White Matter Dissection of the Fetal Brain - Bianca Horgos; Miruna Mecea; Armand Boer; Bianca Szabo; Andrei Buruiana; Florin Stamatian; Carmen-Mihaela Mihu; Ioan Ştefan Florian; Ioan Ştefan Florian; Sergiu Susman; Sergiu Susman; Raluca Pascalau (Frontiers Media S.A., 2020)
Neuroplasticity is a complex process of structural and functional reorganization of brain tissue. In the fetal period, neuroplasticity plays an important role in the emergence and development of white matter tracts. Here, we aimed to study the architecture of normal fetal brains by way of Klingler's dissection. Ten normal brains were collected from in utero deceased fetuses aged between 13 and 35 gestational weeks (GW). During this period, we observed modifications in volume, shape, and sulci configuration. Our findings indicate that the major white matter tracts follow four waves of development. The first wave (13 GW) involves the corpus callosum, the fornix, the anterior commissure, and the uncinate fasciculus. In the second one (14 GW), the superior and inferior longitudinal fasciculi and the cingulum could be identified. The third wave (17 GW) concerns the internal capsule and in the fourth wave (20 GW) all the major tracts, including the inferior-occipital fasciculus, were depicted. Our results suggest an earlier development of the white matter tracts than estimated by DTI tractography studies. Correlating anatomical dissection with tractography data is of great interest for further research in the field of fetal brain mapping.